2012
DOI: 10.1590/1677-553820133806833
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mesenchymal Stem Cells Associated to Matrixen on the Erectile Function in the Rat Model with Bilateral Cavernous Nerve Crushing Injury

Abstract: Objectives:To evaluate the effect of mesenchymal stem cells (MSCs) and MSCs mixed with Matrixen as a cell carrier on the erectile dysfunction caused by bilateral cavernous nerve crushing injury. Materials and Methods: White male Sprague-Dawley rats were divided into 4 groups: sham-operated control group (n = 5), bilateral cavernous nerve crushing group (BCNC group, n = 10), BCNC administered with MSCs group (n = 10,1x106 in 20 µL), BCNC administered with Matrixen group (n = 10.1x106 in 20 µL), BCNC administere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…Scaffolds can place numerous stem cells to a target tissue and possibly get better therapeutic effect in transplantation. Researchers reported improved effects when scaffolds were applied [ 13 , 16 , 22 ]. Our meta-analysis showed that acellular scaffolds could promote cavernous nerve regeneration but were less effective for smooth muscle cell recovery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scaffolds can place numerous stem cells to a target tissue and possibly get better therapeutic effect in transplantation. Researchers reported improved effects when scaffolds were applied [ 13 , 16 , 22 ]. Our meta-analysis showed that acellular scaffolds could promote cavernous nerve regeneration but were less effective for smooth muscle cell recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Kim [ 13 ] reported the effects of BMSCs mixed with Matrixen, a kind of collagen-based biocompatible polymer, and administered to the MPG of rats with cavernous nerve crushed. Four weeks after transplantation, erectile function, PKH-26-labelled BMSCs, expressions of endothelial nitric oxide synthase (eNOS) and nNOS were significantly increased in BMSCs/Matrixen group compared with those in the BMSCs group.…”
Section: Systematic Reviewmentioning
confidence: 99%
“…Similar results were obtained by the same group with the use of ADSC embedded in a nerve growth factor‐loaded hydrogel . Others have used a collagen‐containing gel to retain MSC in close proximity to the MPG and again observed improved erectile recovery and increased penile nNOS expression after cavernous nerve crush injury . In a cavernous nerve resection model, Lin and colleagues showed that bridging the nerve gap with adipose matrix loaded with ADSC resulted in increased cavernous nerve sprouting compared with unseeded matrix; however, because of the model chosen, there was no significant effect on nerve electrical stimulation‐induced intracavernous pressure (ICP) increases .…”
Section: The Use Of Stem Cells For Edmentioning
confidence: 53%
“…We selected studies representing important advances in SC therapy for ED, both in efficacy and in understanding the mechanism of action of cellular therapy. However, all SC studies that were identified using the search criteria noted above are summarised in Table 1 [22–45] .…”
Section: Results and Mechanisms Of Actionmentioning
confidence: 99%